Strategic Planning and Financial Planning in Bina Insani University Business Development Project in Cikarang - Hari Sapto Yudiarso; Tantri Yanuar Rahmat Syah; Suwarto; Rhian Indradewa (Syntax Idea)
Bina Insani University Cikarang has a goal as a university that always upholds the tridharma of higher education which always provides the best in the academic and non-academic fields accompanied by adequate facilities and resources so as to be able to produce graduates who are ready to work and according to the needs of DUDI (Business World and Industrial World). In achieving its goals, Bina Insani University conducts business development planning, one of which is strategic planning and financial planning. This research uses qualitative research methods. The data collection technique in this study uses the literature study method. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. In analyzing strategic planning can be done with the following steps establish Long-Term objectives, the input stage, the matching stage, the decision stage, business level strategy, and learn business canvas model. While financial planning involves 5 main pillars, namely financial target objectives, financial planning elements, financial projections, investment feasibility analysis and financial performance analysis.